Illegibility and Multimodal Writing Practices in Frida Kahlo’s Diary-Codex - Lizarbe Casado, Lucía (Ondina - Ondine, 2025)
Frida Kahlo’s diaristic work, composed in the last years of her life (from 1944 to 1954, albeit intermittently), constitutes an extraordinarily singular example within the landscape of the diary genre, both in the specific Mexican context and within the Latin American tradition. The objectives of this study are, first, to examine the unique space that Frida Kahlo’s diary constructs and, second, to analyze the work through its dual singularity: as a pictorial text and as a collection of textual paintings. This multimodal perspective facilitates the exploration of several key aspects relevant to the study of the diary genre: the significance of the supports and materials, the different layers of writing or the diary as an artistic object. Additionally, this hybrid practice of Kahlo’s, which integrates pictorial and scriptural procedures, makes its status as a work unstable –we will call it a diary-codex, with a certain poetic license–. Consequently, we propose an approach to its illegibility as a form of analysis.Keywords: Frida Kahlo, ilegibility, personal diary, pictorial code, writing